Synthesis and Characterization of Mixed Al,Cu-Pillared and Copper Doped Al-Pillared Bentonite - Ravari, Maryam Hamidi; Sarrafi, Amir; Tahmooresi, Majid (Видавництво Львівської політехніки, 2019)
З використанням зразка бентоніту одер- жано суміші глин, зшитих алюмінієм та міддю (Al, Cu-PILCs) з різним відсотком Cu та імпрегнованих алюмінієм (Cu@Al- PILC). Характеристику зразків проведено за допомогою рентгенівської дифракції, адсорбції-десорбції N2 та Фур‘є- спектроскопії. Визначено, що площа поверхні за БЕТ, загальна площа та об‘єм мікропор Al-PILC зменшуються в Cu@Al- PILC, проте збільшуються у випадку змішаних металів і досягають максимуму для Al, Cu-PILCs. Встановлено, що найвищий вміст міді є в Cu@Al-PILC, тому його каталітичні властивості покращуються. Фур‘є-спектроскопією підтверд- жено введення міді в структуру Al, Cu-PILCs.

In this paper, mixed aluminum and copper pillared clays (Al,Cu-PILCs) with different percentage of Cu and copper impregnated aluminum pillared clay (Cu@Al-PILC) were prepared using a bentonite sample. The samples were characterized by X-ray diffraction, N2 adsorption-desorption and Fourier transformed infrared spectroscopy. The results showed bentonite had a main reflection of montmorillonite that characterized by basal spacing, increased by pillaring. The specific BET surface area, total surface area and micropore volume of Al-PILC decreased in Cu@Al-PILC but increased in the case of mixed metal pillars and the maximum of these parameters related to Al,Cu15-PILC. Maximum weight percentage of copper was in Cu@Al-PILC therefore it contained higher percent of copper and its catalytic properties increased. FTIR result of samples confirmed the successful intercalation of Cu.
Синтез та характеристика суміші Al,Cu-зшитого і промотованого міддю бентоніту
Keywords: алюміній; бентоніт; мідь; зшиті глини; aluminum; bentonite; copper; pillared clays